The effects of bonding temperature and surface roughness on the shear strength of bonded aluminium laminates using polypropylene based adhesive - Ng, Lin Feng; Dhar Malingam, Sivakumar; Subramaniam, Kathiravan; Woo, Xiu Juan; Siva, Irulappasamy (Penerbit Universiti Teknikal Malaysia Melaka, 2019)
The high strength to weight ratio behaviour of aluminium alloys is particularly attractive in the transportation field to reduce the energy consumption. In this study, the effects of bonding temperature and the surface roughness on the single lap shear of bonded aluminium 5052 were studied. The bonding temperatures were in the range of 140°C to 170°C at an interval of 15°C whereas the surface roughness values were at 0.24, 0.49, 0.60 and 0.98. The bonded aluminium sheets were fabricated through the hot compression method in which the adhesives were located between the aluminium sheets. Single lap shear test was conducted at room temperature with reference to ASTM D1002. The results demonstrated that the bonding temperature and surface roughness of aluminium sheets influenced the lap shear strength. The aluminium with surface roughness value of 0.98 evidenced the highest shear strength regardless of bonding temperatures. When comparing the shear strength of aluminium laminates with different bonding temperature, aluminium with 170°C attested a slightly higher shear strength compared to 155°C and 140°C. The shear strength of aluminium with bonding temperature of 170°C was 0.71% and 9.81% higher than 155°C and 140°C respectively at surface roughness value of 0.98.